A variable relevant multi-local PCA modeling scheme to monitor a nonlinear chemical process. (31st December 2021) - You, Lin Xuan; Chen, Junghui
Highlights: The multiple local PCA models are developed for nonlinear multimode processes. The method considers classification and modeling simultaneously. Performances of different monitoring methods of multimode processes are compared. A case study regarding monitoring a real process with multimodes is presented. Abstract: In chemical plants, operated processes require different conditions to produce various product grades and meet the time-to-market demand. Conventional multivariate statistical process control techniques based on a single global model are certainly poor. In the past, data were partitioned first without considering variable correlations before each local model was constructed. This may cause information loss. This study proposes a multi-local principal component analysis (ML-PCA) modeling strategy to monitor a nonlinear process over a large operating region. ML-PCA can automatically enhance the data of the clustered model and weaken those data of the other local models. The operating data are collected from the whole range of operations to cluster and construct the corresponding PCA for each operating condition simultaneously. Once ML-PCA models are constructed, two statistical indices are designed for process monitoring. The effectiveness and accuracy of the proposed ML-PCA are demonstrated through a numerical example and a real industrial process.